2022
DOI: 10.3390/plants11030256
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Viruses Infecting Oats in Korea by Metatranscriptomics

Abstract: Controlling infectious plant viruses presents a constant challenge in agriculture. As a source of valuable nutrients for human health, the cultivation of oats (Avena sativa L.) has recently been increased in Korea. To date, however, few studies have been undertaken to identify the viruses infecting oats in this country. In this study, we carried out RNA-sequencing followed by bioinformatics analyses to understand the virosphere in six different geographical locations in Korea where oats are cultivated. We iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
5
1
Order By: Relevance
“…BYDV is transmitted by the bird cherry-oat aphid ( Rhopalosiphum padi ) and is the most devastating cereal crop virus causing ~11 to 33% of yield loss in wheat fields worldwide [ 48 ]. BYDV infections have been reported in barley, oats, and wheat in Korea [ 43 , 49 ]. Our study identified infections with the BYDV strains PAS and PAV, while other strains, such as CYDV, were not detected.…”
Section: Discussionmentioning
confidence: 99%
“…BYDV is transmitted by the bird cherry-oat aphid ( Rhopalosiphum padi ) and is the most devastating cereal crop virus causing ~11 to 33% of yield loss in wheat fields worldwide [ 48 ]. BYDV infections have been reported in barley, oats, and wheat in Korea [ 43 , 49 ]. Our study identified infections with the BYDV strains PAS and PAV, while other strains, such as CYDV, were not detected.…”
Section: Discussionmentioning
confidence: 99%
“…Current species demarcation criteria within the Luteoviridae family take into account >10% differences in aa sequences of any viral gene product [24]. BYDV-PAS has been confirmed in many countries around the world: the USA [25], New Zealand [26], Republic of Korea [27], Morocco [28], and in Europe-France [29], Czech Republic [30], Poland [18], Estonia [31]. However, the real BYDV-PAS occurrence might be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been introduced into more plant virome studies and diagnostic purposes ( Villamor et al, 2019 ). Virome studies on fruit trees using RNA-seq have been extensively employed in the past few years ( Jo et al, 2018a , 2020 ; Kim et al, 2022 ). However, few studies have been performed on the virome in fruit pollen samples ( Jonghe et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%